Low temperature district heating in Austria: Energetic, ecologic and economic comparison of four case studies. (1st September 2016) - Köfinger, M.; Basciotti, D.; Schmidt, R.R.; Meissner, E.; Doczekal, C.; Giovannini, A.
Abstract: Feasibility of district heating networks for areas with low heat demand of passive and low energy houses implies the development of innovative concepts for the production, storage, distribution and supply of thermal energy. Low supply temperatures enables the use of heat from renewable and alternative sources, currently been neglected due to the usually high supply temperatures used in conventional district heating systems. Further on, low network temperatures are supporting the reduction of operational and investment costs. The paper describes the development of economically and ecologically optimized concepts for low temperature district heating networks using four representative case studies in Austria: Aktivpark Güssing, Seestadt Aspern, Winklweg Siedlung and Hummel Kaserne. The four case studies offered the possibility to investigate different supply and demand connection schemes and consequently deriving optimized scenarios taking into account local framework conditions, such as consumption and production settings and the related control strategies. The scenarios analysis is performed considering both economic and ecological issues. The results of the study show that the availability and economic conditions of low temperature heat sources is a key factor for facilitating LTDH networks. In rural areas, lower heat losses due to lower network temperatures are beneficiary for the LTDH network performance. Highlights: Low temperature district heating concepts for space heating and domestic hot water. Connection concepts including booster heater for hygienic DHW preparation. Simulation based comparison of four case studies in Austria. Energetic, ecologic and economic evaluation of different concepts and scenarios.